2020
DOI: 10.1186/s13054-020-2819-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of initial infusion rates of fluid resuscitation on outcomes in patients with septic shock: a historical cohort study

Abstract: Background: Fluid resuscitation has become the cornerstone of early septic shock management, but the optimal fluid rate is still not well studied. The goal of this investigation is to examine the relationship between fluid resuscitation rate and septic shock resolution. Method: We retrospectively studied adult (≥ 18 years) patients with septic shock, defined based on sepsis III definition, from January 1, 2006, through May 31, 2018, in the medical intensive care unit (MICU) of Mayo Clinic Rochester. The fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…The study further showed that an initial uid resuscitation rate of 20-30 ml/kg within the rst 1 h or completion of the initial 30 ml/kg uid resuscitation between the rst 1-2 h may be associated with faster organ function recovery and lower 28-day mortality in patients with septic shock. This nding is consistent with a recent retrospective study [10], which found that an initial uid resuscitation rate of 0.25-0.50 ml/kg/min may be associated with early septic shock reversal and lower 28-day mortality compared with slower rates of infusion. Thus, using an appropriate initial uid resuscitation rate may improve the prognosis of patients with septic shock.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The study further showed that an initial uid resuscitation rate of 20-30 ml/kg within the rst 1 h or completion of the initial 30 ml/kg uid resuscitation between the rst 1-2 h may be associated with faster organ function recovery and lower 28-day mortality in patients with septic shock. This nding is consistent with a recent retrospective study [10], which found that an initial uid resuscitation rate of 0.25-0.50 ml/kg/min may be associated with early septic shock reversal and lower 28-day mortality compared with slower rates of infusion. Thus, using an appropriate initial uid resuscitation rate may improve the prognosis of patients with septic shock.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, septic shock patients who completed 30 ml/kg initial uid resuscitation between the rst 1-2 h had a lower 28-day mortality rate and faster organ function recovery. This nding is consistent with a recent retrospective study, which found that an initial uid resuscitation rate of 0.25-0.50 ml/kg/min may be associated with early shock reversal and lower 28-day mortality compared with slower rates of infusion [16]. In addition, this study showed that insu cient initial uid resuscitation (below 20 ml/kg within the rst 1 h) may increase 28-day mortality in these patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From January 1, 2006, to May 31, 2018, 217,696 patients were admitted to ICUs and 19,773 patients were admitted to MICU at the Mayo Clinic, Rochester. Among these MICU patients, 2,241 patients had septic shock, but only 1,052 individuals had initial resuscitation at MICU (this cohort is previously reported elsewhere [15]), and of those, 229 (22%) developed AKI and initiated kidney replacement therapy at the MICU. Among 158 ICU survivors, 73 (46%) patients were weaned from RRT in ICU and 85 (54%) were transitioned to intermittent RRT.…”
Section: Resultsmentioning
confidence: 63%
“…Typically, fluid in the resuscitation phase was given rapidly, with the rate at least 500 ml over 15 min or 2000 ml/h [ 2 ]. A recent study revealed that completion of the initial 30 ml/kg fluid resuscitation within 2 h was associated with faster shock resolution and decreased sepsis mortality when compared with a slower infusion rate [ 3 ].…”
Section: Introductionmentioning
confidence: 99%